PENGARUH PERPUTARAN PIUTANG TERHADAP PROFITABILITAS PADA PT TRIJAYA MAKMUR LESTARI - KARYADI; LUKMAN NULHAKIM LUKMAN NULHAKIM (POLITEKNIK PIKSI GANESHA, 2019)
The main objective of the research is to analyze the influence of account receivable turnover to the profitability of PT Trijaya Makmur Lestari The method used in this study was a quantitative research, which took the examples of financial report period January until December 2015. The data collection method was used in this research was done by observation and literature study. Meanwhile the techniques used to analyze the data were linier regression analysis, the correlation test, analysis of the coefficient of determination and t testBased on the result analysis, the correlation obtained 0,498 means between account receivable turnover and profability medium correlated. Meanwhile the coefecient determibation between account receivable turn over to profability 24,8%, while the rest 75,2% influenced by other variabels that is not described in this research. From the research conducted, the problem is theexistence of which paid the credit of sales debt not on time. The suggestions given are to evaluate the business relationship with the outlets which ofte in arrears, by limiting the maximum amount of purchase credit, increasing the price or reduce the rebate to the outlet of local genuine income on intensification or extensification; 2) the company more thorought in managing expense,especially capital expense.